Marker assisted breeding to develop multiple stress tolerant varieties for flood and drought prone areas - Sandhu, Nitika; Dixit, Shalabh; Swamy, B. P. M.; Raman, Anitha; Kumar, Santosh; Singh, S.P.; Yadaw, R.B.; Singh, O.N.; Reddy, J.N.; Anandan, A.; Yadav, Shailesh; Venkataeshwarllu, Challa; et al. (Springer, 2019)
"Climate extremes such as drought and flood have become major constraints to the sustainable rice crop productivity in rainfed environments. Availability of suitable climate-resilient varieties could help farmers to reduce the grain yield losses resulting from the climatic extremities. The present study was undertaken with an aim to develop high-yielding drought and submergence tolerant rice varieties using marker assisted introgression of qDTY1.1, qDTY2.1, qDTY3.1 and Sub1. Performance of near isogenic lines (NILs) developed in the background of Swarna was evaluated across 60 multi-locations trials (MLTs). The selected promising lines from MLTs were nominated and evaluated in national trials across 18 locations in India and 6 locations in Nepal Grain yield advantage of the NILs with qDTY1.1 + qDTY2.1 + qDTY3.1 + Sub1 and qDTY2.1 + qDTY3.1 + Sub1 ranged from 76 to 2479 kg ha− 1 and 396 to 2376 kg ha− 1 under non-stress (NS) respectively and 292 to 1118 kg ha− 1 and 284 to 2086 kg ha− 1 under reproductive drought stress (RS), respectively. The NIL, IR96322–34-223-B-1-1-1-1 having qDTY1.1 + qDTY2.1 + qDTY3.1 + Sub1 has been released as variety CR dhan 801 in India. IR 96321–1447-651-B-1-1-2 having qDTY1.1 + qDTY3.1 + Sub 1 and IR 94391–131–358-19-B-1-1-1 having qDTY3.1 + Sub1 have been released as varieties Bahuguni dhan-1′ and ‘Bahuguni dhan-2’ respectively in Nepal. Background recovery of 94%, 93% and 98% was observed for IR 96322–34-223-B-1-1-1-1, IR 96321–1447-651-B-1-1-2 and IR 94391–131–358-19-B-1-1-1 respectively on 6 K SNP Infinium chip The drought and submergence tolerant rice varieties with pyramided multiple QTLs can ensure 0.2 to 1.7 t ha− 1 under reproductive stage drought stress and 0.1 to 1.0 t ha− 1 under submergence conditions with no yield penalty under non-stress to farmers irrespective of occurrence of drought and/or flood in the same or different seasons."